Encarceramento em massa como política social nos Estados Unidos e Brasil (Altre Modernità, 2019)
Both the United States and Brazil have undergone major changes in social policies. The replacement of the welfare state by a police state today, in practice, demonstrates the excessive criminalization of marginality that generates punitive restraint that affects mainly the poor and, above all, the black population. This article approaches this relationship through a bibliographical review and has as main finding the similarities between Brazil and the United States in its social construction that leads to mass incarceration.